Life-Threatening Coronary Disease is Prevalent in Patients with Stenosing Carotid Artery Disease. Issue 8 (December 2015) - Nuotio, Krista; Soinne, Lauri; Hänninen, Helena; Saksi, Jani; Tuimala, Jarno; Jula, Antti; Kovanen, Petri T.; Kaste, Markku; Ijäs, Petra; Lindsberg, Perttu J.
Background: Atherosclerosis affects several vascular trees systemically and though surgical plaque removal diminishes the risk of stroke in patients with carotid stenosis, they still face a risk of other atherothrombotic complications like myocardial infarction and premature death. Aims and/or hypothesis: This study was designed to reveal the long-term risk of death and atherothrombotic events following carotid endarterectomy. Methods: Eighty-nine previously (1997–2000) endarterectomized carotid patients (56–92 years) were followed up to 15·2 years. Causes of death, cardiovascular events (stroke, transient ischemic attack, acute myocardial infarction), comorbidities, and medications were recorded and analyzed by Cox regression analysis. Four population controls and four controls with coronary disease ( n = 712) were selected for each case from a population cohort for age- and gender-matched analysis. Results: At the end of follow-up, 41 (44·6%) patients had died and 48 were alive. Ten patients (24, 4%) died due to acute myocardial infarction and one (2, 4%) due to stroke. Nineteen (21%) patients had an acute myocardial infarction, 12 (13%) had a stroke, 13 (15%) had a transient ischemic attack, and 5 (6%) had other atherothrombotic events. The risk of death was 5·7-fold in diabetics ( P < 0·001) and 3·9-fold in smokers ( P < 0·001). Patients who did not use statins had 5·0-fold, and irregular users 3·3-fold risk of death compared with active users ( P = 0·005 and P = 0·001, respectively). The major factors associated with acute myocardial infarction were diabetes (6·0-fold risk, P = 0·004), bilateral carotid disease (3·5-fold risk, P = 0·014), and lack of statin use (4·4-fold risk, P = 0·038). Compared with population controls, carotid patients had a 4·4-fold risk of acute myocardial infarction ( P = 0·002). Conclusions: Endarterectomized carotid patients have a high risk of acute myocardial infarction and death, and need an intensified cardiovascular disease-risk-lowering treatment. Although asymptomatic, the evaluation of prognostically significant myocardial ischemia should be considered in these high-risk patients. Eventually, a clinical trial is needed to address whether carotid patients would benefit from early intervention.